AB1279-HPR A DESCRIPTIVE STUDY RELATED TO THE ADHERENCE BEFORE AND AFTER ENROLLING IN A MULTIDISCIPLINARY EDUCATIONAL PROGRAM. (2nd June 2020) - Buitrago-Garcia, D.; Rodriguez, F.; Sánchez, G.; Santos-Moreno, P.
Abstract : Background: Rheumatoid arthritis (RA) is an inflammatory, chronic disease. It leads to deformity and destruction of joints through the erosion of cartilage and bone. Patients with RA report to suffer symptoms in hands, joints, swelling, loss of motion, muscle weakness among others.(1).Centers of excellence in RA have proposed a multidisciplinary model of care with an initial diagnosis, treatment prescription and follow-up with a rheumatologist, periodic consultations with a physiatrist, psychologist, physiotherapist, occupational therapy, nutrition and a patient focused program(2). With this model of care, the patient is seen as a whole, and the expectation is to achieve the best results in the management of RA. However, if the patient does adhere the model becomes ineffective. Objectives: The aim of this to report the attendance to a multidisciplinary model of care for patients with RA that attend to a specialized center in Colombia, before and after enrolling in a educational program. Methods: We performed a descriptive study. Patients enrolled our educational program in July 2019. In our institution patients are followed-up under T2T standards and a multidisciplinary approach, as part of our model of care they have periodic consultations with a rheumatology, physiatrist, psychologist, physiotherapist, occupational therapy and nutrition. We collected sociodemographic data, DAS28, and compare the attendance to each specialty at the beginning and at 6-month follow-up. Descriptive epidemiology was done, we calculated means, and standard deviations for continuous variables and categorical variables were presented as rates. We compared disease activity and adherence at the beginning of the program and after six months of attendance. Results: We included 229 patients; mean age was 59 years ±10; 93% were female. At the beginning of our program, mean DAS28 was 2.57 ± 1.19, from all patients 65% were at remission, 11% at low disease activity 19% at moderate disease activity and, 5% at severe disease activity. Regarding adherence to our model, the medical specialty with the highest attendance was rheumatology (30%) followed by, physical therapy (16%) physiatrist consultation (15%) psychology (13%) and, occupational therapy (11%); the specialty with the lowest attendance was nutrition (8%). After six months of attendance to the educational program, we found an increasing number of patients in remission 67%, low disease activity 15%, moderate disease activity 18%, we did not have patients with severe DA28. Regarding the medical specialties, we found a 3% rise in the attendance to the nutrition consultation and psychology consultation. We did not find statistical association between disease activity and adherence to the model. Conclusion: These results are a clear example of how an educational program is capable of increasing awareness and improving the clinical outcomes and adherence to a multidisciplinary model for approaching RA. As other studies have shown(3), patient education interventions improve adherence to medication and to attendance to health care specialists. References: [1]Santos-Moreno P, Castaneda O, Garro B, Flores D, Sanchez G, Castro C. From the model of integral attention to the creation of centers of excellence in rheumatoid arthritis. Clinical rheumatology. 2015;34 Suppl 1:S71-7. [2]Taibanguay N, Chaiamnuay S, Asavatanabodee P, Narongroeknawin P. Effect of patient education on medication adherence of patients with rheumatoid arthritis: a randomized controlled trial. Patient preference and adherence. 2019;13:119-29. Acknowledgments: This project has been funded by a collaboration between the Ministry of Science, Technology and Innovation COLCIENCIAS (contract 746-2018), the Fundación Universitaria de Ciencias de la Salud and Biomab - Center for Rheumatoid Arthritis Disclosure of Interests: Diana Buitrago-Garcia: None declared, Fernando Rodriguez: None declared, GUILLERMO SÁNCHEZ: None declared, Pedro Santos-Moreno Grant/research support from: I have received research grants from Abbvie, Biopas-UCB, Janssen, Novartis, Pfizer., Speakers bureau: I have been a speaker for Abbvie, Biopas-UCB, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi.